2020
DOI: 10.2147/dddt.s273322
|View full text |Cite
|
Sign up to set email alerts
|

<p>Stoichiometrically Governed Curcumin Solid Dispersion and Its Cytotoxic Evaluation on Colorectal Adenocarcinoma Cells</p>

Abstract: Background Colorectal cancer (CRC) is the third most commonly occurring cancer in men and the second most commonly occurring cancer in women. Curcumin (CMN) is obtained from a natural source and has no toxicity, even at high doses (8,000 mg/kg body weight in 24 hours) and was determined to have anticancer potency on several kinds of carcinoma. However, its medical applications were limited because of its low solubility and poor bioavailability. Materials and Methods To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Therefore, the optimal ratio of 1 : 2 was selected for the further preparation of IR and SR granules [ 19 ]. This optimized ratio gave an impact of solubility on IR and SR which is given in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the optimal ratio of 1 : 2 was selected for the further preparation of IR and SR granules [ 19 ]. This optimized ratio gave an impact of solubility on IR and SR which is given in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that the DL efficiency of nanoparticles was increased on drug concentration and polymer concentration increased [ 19 ]. It was also noticed that the combination of hydrophilic and hydrophobic polymers at a 1 : 1 ratio encapsulated the drug up to 87.5% which was more than that of using a single polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess of samples (CMN, PM, and SC) with double distilled water were taken in a 50 mL Eppendorf tube and placed on a constant water bath, and temperature was maintained at 37 ± 0.5 °C for 24 h and shaken at 30 min intervals [ 45 ]. Subsequently, the contents were filtered through a 0.45 µm Millipore membrane filter, diluted suitably, and the UV absorbance was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The structural appearance revealed a lighter core encompassed by a denser border that perfectly enclosed the center. When a thin lipid layer is hydrated, it develops enclosed vesicular network that supports in shape from spherical to circular in order to achieve thermodynamic stability by lowering the systems total free energy [19]. Even after applying various mechanical loads such as sonication and extrusion, no disturbances in vesicular structure proved vesicle integrity (Figure 1b).…”
Section: Itz-npevs Shapementioning
confidence: 99%